Human T cells loaded with superparamagnetic iron oxide nanoparticles retain antigen-specific TCR functionality - Pfister, Felix; Dörrie, Jan; Schaft, Niels; Buchele, Vera; Unterweger, Harald; Carnell, Lucas R.; Schreier, Patrick; Stein, Rene; Kubánková, Markéta; Guck, Jochen; Hackstein, Holger; Alexiou, Christoph; et al. (Frontiers in Immunology, 2023)
Immunotherapy of cancer is an emerging field with the potential to improve long-term survival. Thus far, adoptive transfer of tumor-specific T cells represents an effective treatment option for tumors of the hematological system such as lymphoma, leukemia or myeloma. However, in solid tumors, treatment efficacy is low owing to the immunosuppressive microenvironment, on-target/off-tumor toxicity, limited extravasation out of the blood vessel, or ineffective trafficking of T cells into the tumor region. Superparamagnetic iron oxide nanoparticles (SPIONs) can make cells magnetically controllable for the site-specific enrichment. In this study, we investigated the influence of SPION-loading on primary human T cells for the magnetically targeted adoptive T cell therapy. For this, we analyzed cellular mechanics and the T cell response after stimulation via an exogenous T cell receptor (TCR) specific for the melanoma antigen MelanA or the endogenous TCR specific for the cytomegalovirus antigen pp65 and compared them to T cells that had not received SPIONs. SPION-loading of human T cells showed no influence on cellular mechanics, therefore retaining their ability to deform to external pressure. Additionally, SPION-loading does not impair the T cell proliferation, expression of activation markers, and cytokine secretion after antigen-specific activation mediated by the TCR. In summary, we demonstrated that SPION-loading of T cells does not impair cellular mechanics or the functionality of the endogenous or an exogenous TCR, which allows future approaches using SPIONs for the magnetically enrichment of T cells in solid tumors.